Arbitration in air, space and telecommunications law : enforcing regulatory measures (Kluwer Law International The HagueNL, 2002)
Examines the international instruments in air, space and telecommunications law and the need for a mandatory supranational dispute settelment mechanism. Deals with the European Organization for the Safety of Air Navigation draft Arbitration Policy in great depth. Reviews the experiences of the European Space Agency and the International Telecommunications Union with respect to dispute settlement. Considers general issues of pre-arbitration procedures, expedited arbitration, enforcement and the need for specialist espertise.
Keywords: SPACE LAW